Pemberdayaan Literasi Al-Qur’an Melalui Pendampingan Tahsin Ibu-Ibu di Desa Tangkit Muaro Jambi - Zulaika, Zulaika; Vahlepi, Sahrizal (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2025)
This study aims to improve Qur’an reading proficiency with tartīl and tajwīd through a community-based tahsin program using behaviorist, andragogical, and living Qur’an approaches. The two-day program combined classical methods for strengthening tajwīd theory and talaqqi musyāfahah for personalized coaching. A total of 35 mothers participated through a participatory recruitment process, supported by local leaders and university students. Evaluation tools included pre-tests, post-tests, direct observation, and tutor assessment sheets. The results showed significant improvements in makhārijul ḥurūf articulation, proper intonation, and reading confidence. A self-sustained Qur’anic study group emerged at the neighborhood level (RT), continuing the learning process independently. The novelty of this study lies in the integration of three pedagogical approaches within a contextual, community-based learning model, as well as in the empowerment of village women as agents of religious literacy within the family. The program demonstrates the potential of tahsin as a vehicle for sustainable social and religious transformation. Further development is recommended through a community tahsin curriculum, advanced training, and cross-institutional collaboration to strengthen Qur’anic culture at the grassroots level.